Analyzing Marketing Initiatives in India Higher Education - Kelkar, Mohit (Digital Repository of Theses - SSBM Geneva, 2024)
Higher education institutions in India are increasingly recognizing the importance of effective marketing strategies to attract students, enhance institutional visibility, and maintain competitiveness in the educational landscape. This research paper delves into the marketing initiatives undertaken by higher education institutions in India from a strategic perspective. This research study employs a mixed-method approach to investigate and analyze the marketing initiatives in higher education institutions in India. The study aims to provide a comprehensive understanding of the marketing strategies adopted by Indian higher education institutions and their impact on student enrollment, institutional reputation, and overall effectiveness. The qualitative component of the research involves in-depth interviews with university administrators, marketing professionals, and students to explore their perspectives on marketing initiatives in higher education. Through these interviews, the study seeks to uncover the key strategies, challenges, and successes in implementing marketing campaigns within the Indian higher education context. In addition to qualitative interviews, the research incorporates a quantitative survey to gather data on the effectiveness of various marketing channels, student preferences, and the influence of marketing on enrollment decisions. The survey aims to quantify the impact of marketing initiatives on student recruitment and institutional branding. By combining qualitative insights with quantitative data analysis, this research seeks to provide a holistic view of marketing initiatives in higher education from an Indian perspective. The mixed-method approach allows for a comprehensive exploration of the complexities and nuances of marketing strategies in the Indian higher education sector. The findings of this study are expected to contribute valuable insights to higher education administrators, marketing professionals, and policymakers in India. By understanding the effectiveness of marketing initiatives and their influence on student engagement and enrollment, institutions can make informed decisions to enhance their marketing strategies and achieve their recruitment goals in a competitive educational landscape.